Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis

Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste

Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites